STUNTING PADA ANAK YANG MENGALAMI TUBERKULOSIS - HANIF, HANIF; NURCAHAYA, NURCAHAYA (LP2MTBM MAKARIOZ, 2023)
Neuroendocrine differentiation in breast cancer recognized since 1963 but hindered by frequently changing terminology and diagnostic criteria. Breast Carcinoma of No Special Type with neuroendocrine differentiation (IBC-NST-NE) is diagnosed by identifying the presence and extent of NE features. This case report emphasize the significance of establishing IBC-NST-NE diagnose. A 75-year-old woman presented with a year-old left breast lump, rapidly enlarging over 3 months with multiple ulceration and bloody nipple discharge. Needle biopsy confirmed ductal carcinoma. Radical mastectomy revealed a 7,5x7,3x4,9 cm, gray-white, lobulated mass with indistinct borders. Histopathology identified invasive ductal carcinoma with 30% exhibiting NE features—arranged in insular and pseudorosette pattern, composed of polygonal cells with granular cytoplasm and salt-and-pepper chromatin. Synaptophysin and chromogranin A were positive in neuroendocrine component leading to the IBC-NST-NE diagnosis. Therapy of IBC-NST-NE follow standard IBC protocol, however it have shorter disease-free survival , poorer survival rate, higher distant metastasis rates and higher TNM stage at diagnosis. Diagnosing IBC-NST-NE is crucial for prognosis and enhance our understanding of neuroendocrine differentiation behaviour in breast cancer.